2011
DOI: 10.1111/j.1751-553x.2010.01288.x
|View full text |Cite
|
Sign up to set email alerts
|

CIP2A is over‐expressed in acute myeloid leukaemia and associated with HL60 cells proliferation and differentiation

Abstract: Summary Introduction:  CIP2A is a newly identified inhibitor of PP2A. It can stabilize c‐Myc and promote anchorage‐independent cell growth and tumour formation. CIP2A is over‐expressed in some solid tumours although its expression in acute myeloid leukaemia (AML) is still unknown. Methods:  CIP2A mRNA and protein expressions were determined in bone marrow mononuclear cells of both patients with AML and healthy controls using reverse transcription polymerase chain reaction and Western blot, respectively. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 28 publications
0
48
1
Order By: Relevance
“…It has been shown that CIP2A deletion results in a reduction of oncogenic potential for multiple tumors (20,26,32). Furthermore, SET knockdown was shown to negatively affect tumorigenesis in blast crisis chronic myelogenous leukemia (33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CIP2A deletion results in a reduction of oncogenic potential for multiple tumors (20,26,32). Furthermore, SET knockdown was shown to negatively affect tumorigenesis in blast crisis chronic myelogenous leukemia (33).…”
Section: Discussionmentioning
confidence: 99%
“…16 CIP2A has recently been shown to be overexpressed in AML patients and correlated with relapse after treatment. 17 A single case study has reported a CIP2A-MLL translocation in infant AML. 18 Nothing is known about CIP2A expression and function in CML.…”
Section: Introductionmentioning
confidence: 99%
“…CIP2A is a widespread oncogenic factor in human neoplasms (4)(5)(6)(7)(8)(9)3). Similar to the Ras oncogene, CIP2A is required for anchorage-independent cell growth and malignant transformation of human cells (4).…”
Section: A B C Discussionmentioning
confidence: 99%
“…Previous studies have shown that CIP2A serves a critical role in the progression of several cancer types, including head and neck squamous cell carcinoma, oral squamous cell carcinoma, oesophageal squamous cell carcinoma, colon, gastric, breast, prostate, tongue, lung, cervical cancer and acute myeloid leukaemia (3)(4)(5)(6)(7)(8)(9). In 2009, Côme et al (10) demonstrated that CIP2A is associated with clinical aggressivity in human breast cancer and promotes the malignant growth of breast cancer cells (10).…”
Section: Introductionmentioning
confidence: 99%